Satellite Monitoring of Small-scale Farming Systems in Subang, Indonesia - Bambang H. Trisasongko; Dyah R. Panuju; La Ode S. Iman (Institute for Research and Community Services (LPPM) ITB, 2012)
Rice fields in Java, Indonesia have been in tremendous threat due to land policy weaknesses. In order to ensure food supply, satellite-based monitoring scheme has been chosen to accommodate quick data acquisition for agriculture planning. Nonetheless, detailed rice field map is lacking and it should be taken in consideration. WorldView-2 has the highest ground resolution to date, which is suitable to construct new rice distribution map in Indonesia. This paper shows that panchromatic data of the sensor have capability in identification of fragmented rice fields and clearly showed galengans. Red edge and Coastal bands introduced by WorldView-2 were found substantial to rice growth discrimination. In addition, various rice growth periods were detectable which helped to create of rice status map at appropriate accuracy.